Carcass traits and value of meat and byproducts of buffalo - MUTHUKUMAR, M; KANDEEPAN, G; PATHAK, VIKAS; RATHOD, K S; AMBADKAR, R K; KULKARNI, V V (The Indian Journal of Animal Sciences, 2018)
A study was conducted to collect data on carcass traits covering 1,005 buffaloes across India. The results indicated that the live weight and dressed carcass weight of buffaloes ranged from 174.82 to 422.83 kg and 79.08 to 213.73 kg, respectively with an average dressing percentage of 47.92%. There was a significant difference in the overall dressing percentage and overall yield of blood, skin and intestine of buffaloes of different body weight groups, viz. less than 200 kg (group 1), between > 200 to 300 to 300 to >400 kg (43.08%) and >200 to